ROLE OF MORPHO-ANATOMICAL VARIATIONS AND CHLOROPHYLL IN IMPARTING RESISTANCE TO GROUNDNUT AGAINST LATE LEAF SPOT (Journal of Plant Disease Sciences, 2017)
Static morphological and anatomical variations of healthy and biochemical constituents of healthy and Late Leaf spot (LLS) Phaeoisariopsis personata infected ten resistant groundnut genotypes including two wild genotypes viz., RHRG 6083, GPBD 4, KDG 128, ICG 11426, ICG 12672, ICG 13919, ICG 14475, ICGV 94118, ICGV 13160 and ICGV 13165 and two susceptible ones viz. SB XI JL 24 were evaluated. The foliage of resistant genotypes were and characterized by small sized with less number of stomata, higher frequency of trichomes, greater thickness of epidermis cum cuticle. The susceptible foliage was showed high frequency of large sized stomata, less thickness of epidermis-cum cuticle layer, few trichomes on lower leaf surface. The content of chlorophyll was found more in resistant than susceptible genotypes. There was reduction in chlorophyll content after inoculation of the pathogen in all groundnut genotypes. These differences were considered as partial contributing morphological, anatomical and biochemical features of defense system of groundnut to LLS.